Who calls it? Actors and accounts in the social construction of organizational moral failure - Shadnam, Masoud; Crane, Andrew; Lawrence, Thomas B. (My University, 2020)
In recent years, research on morality in organizational life has begun to examine how organizational conduct comes to be socially constructed as having failed to comply with a community’s accepted morals. Researchers in this stream of research, however, have paid little attention to identifying and theorizing the key actors involved in these social construction processes and the types of accounts they construct. In this paper, we explore a set of key structural and cultural dimensions of apparent noncompliance that enable us to distinguish between four categories of actors who engage in constructing the label of moral failure: dominant insiders, watchdog organizations, professional members, and publics. The analysis further clarifies which category of actor is more likely to succeed in constructing the label of moral failure under which circumstances, and what accounts they are likely to use, namely scapegoating, prototyping, shaming, and protesting.
Keywords: account; actor; label; legitimacy; moral failure; morality; social construction; surveillance